A novel computer vision‐based monitoring methodology for vehicle‐induced aerodynamic load on noise barrier. Issue 12 (3rd October 2018) - Pan, Yue; Wang, Dalei; Shen, Xiang; Xu, Yusheng; Pan, Zichao
Summary: Due to the absence of antifatigue design under vehicle‐induced aerodynamic load (VIAL) during the process of structural design, structural failures of noise barriers erected on urban highway viaducts have become a common issue in China. In this paper, a novel VIAL monitoring methodology is proposed, which can achieve a remote VIAL measuring only by analysis and application of the data from a traffic‐monitoring camera. To establish this methodology, a VIAL determinative model and a computer vision system for measuring the vehicle running characteristics are developed. The accuracy and reliability of this methodology have been validated by a field experiment. By comparing with the results of vehicle‐induced aerodynamic pressure (VIAP) from a sensor‐based wind pressure acquisition system, it was found that the systemic root mean square deviations of maximum and minimum values of VIAP were 12.13% and 10.10%, respectively.